The Dual Challenge: Expanding Equal Access and Ensuring Quality in Cameroon’s Higher Education - Tanyu, Ngenge Ransom; Rofiah, Khofidotur; Ashu, Frederick Ebot; Jude, Chuye Giyoh (International Journal of African Higher Education, 2026)
Cameroon’s higher education sector has expanded significantly since the 1960s, growing from one federal university to eleven public and 430 private universities today, with student enrolment rising from 539 to over 350,000. This article examines the tension between increasing access and ensuring quality within Cameroon’s dual Anglo-Saxon and Francophone systems. To critically assess the interplay between increased access and educational quality, we adopted a mixed-methods research strategy, including a structured survey of 109 stakeholders, supplemented by a few qualitative online interviews. The results show that while economic and population factors drive growth, poor research output (27.5% of respondents), governance problems (22%) and limited funding (14.7%) make it harder to maintain quality. Over 73% of participants believe that quality has not matched quantitative growth, with financial constraints (56%) and outdated curricula noted as key barriers. Public universities dominate rankings, yet private ones suffer from inadequate oversight, part-time staffing and low wages (e.g., 1,500–3,000 CFA per hour) (1USD=555 FCFA). The article highlights the need for curriculum reform (50.5% priority), faculty training and accreditation strengthening, decentralised governance, increased investment and quality assurance to enhancing graduate employability and equity.